Mechanical properties evaluation of ReBCO CICC jacket based on super-austenitic stainless steel for CFETR high-field magnet. (March 2023) - Wang, Weijun; Zhao, Chuanyi; Jin, Huan; Huang, Chuanjun; Li, Laifeng; Tu, Zhengping; Xu, Bin; Zhai, Ruzong; Li, Jiangang; Qin, Jinggang
Highlights: The jacket of CICC was prepared by N50 material for the first time. The low temperature strength of N50 jacket is much higher than that of ITER conductor jacket. Area of over 1500 MPa yield stress and over 130 MPa√m fracture toughness is a new target for ReBCO CICC jacket. Development policy of a new cryogenic structural material was presented for CFETR. Abstract: To excite stronger magnetic fields, high temperature superconducting (HTS) insert coils are planned for the next generation central solenoid magnet for China fusion engineering test reactor (CFETR). The development of high strength and high toughness jacket has become one of the challenges in the application of high-field cable-in-conduit conductors (CICC). 0.2 % proof stress of jacket should be over 1500 MPa at 4.2 K for HTS conductors, thus 316LN and JK2LB jackets developed by ITER do not meet the requirements. Nitronic 50 (N50) super-austenitic stainless steel material has great optimization potential for the development of jacket. Based on the modified N50 material, China prepared the CICC jacket and has done some R&D work on the N50 jacket. The entire process of ReBCO CICC preparation, including extrusion, bending and straightening, was simulated using the N50 stainless steel jacket. The N50 circle-in-square jackets prepared in China showed a yield strength greater than 1600 MPa and a fracture toughness KIC better than 110 MPa·m 1/2 after cold work at 4.2 K. This paper will focus on the preparation, cold work processing and performance test of the N50 jacket. This study will present experimental data and discuss the feasibility of modified N50 as a high-magnetic field jacket material for next-generation fusion reactors.